2014
DOI: 10.5815/ijieeb.2014.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Computational Intelligence in Magnetic Resonance Imaging of the Human Brain: The Classic-Curvature and the Intensity-Curvature Functional in a Tumor Case Study

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…MRI provides the information related to the anatomy of the pathology and such information is used in order to classify the tumor. The tumor embeds in its structure the key to the correct diagnosis and moreover embeds details that can be enhanced through the post-processing of the MRI images [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…MRI provides the information related to the anatomy of the pathology and such information is used in order to classify the tumor. The tumor embeds in its structure the key to the correct diagnosis and moreover embeds details that can be enhanced through the post-processing of the MRI images [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to frame into the literature the works of this research, which recalls works reported earlier [7,[12][13][14][15][16][17], it is necessary to consider the rationale of the study presented in this paper. So far, no studies have been reported attempting to achieve the characterization of the intensity-curvature term before interpolation.…”
Section: The Scope Of the Researchmentioning
confidence: 99%
“…The classic-curvature images have been object of considerable study [7,12,14,17] and allow to distinguish clearly the brain tumor. Moreover, similarly to the original MRI image, the classic-curvature image shows a clear layout of the tumor and the surrounding brain structures.…”
Section: The Scope Of the Researchmentioning
confidence: 99%
See 2 more Smart Citations